2022
DOI: 10.1093/ofid/ofac639
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Coronavirus Disease 2019 Pandemic on Antiretroviral Therapy Initiation and Care Delivery for People With Newly Diagnosed HIV in an Integrated Healthcare System

Abstract: The COVID-19 pandemic disrupted health systems. For patients newly diagnosed with HIV, starting immediate antiretroviral therapy (ART) is recommended. For periods before and during the COVID-19 pandemic, Kaiser Permanente Northern California found similar rates of rapid ART initiation and time to viral suppression, concurrently with an increase in telemedicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Another limitation of our study is that a portion of the follow-up period occurred during the COVID-19 pandemic, which may have affected laboratory data, follow-up visits, and missing data. However, in a separate analysis of this study, no statistically significant differences were found in care delivery in our cohort before or during the COVID-19 pandemic [ 33 ]. Finally, there were missing data on viral load measurements for 9.7% of patients, which may have introduced bias into the analysis of cumulative viremic burden.…”
Section: Discussionmentioning
confidence: 95%
“…Another limitation of our study is that a portion of the follow-up period occurred during the COVID-19 pandemic, which may have affected laboratory data, follow-up visits, and missing data. However, in a separate analysis of this study, no statistically significant differences were found in care delivery in our cohort before or during the COVID-19 pandemic [ 33 ]. Finally, there were missing data on viral load measurements for 9.7% of patients, which may have introduced bias into the analysis of cumulative viremic burden.…”
Section: Discussionmentioning
confidence: 95%